Lack of information and possible risks about overuse of the next day pill (levonorgestrel) (Research, Society and Development, 2021)
Introduction: The emergency contraceptive was initially developed by Canadian physician Albert Yuzpe in 1972, in which he formulated a combination of estrogen and progesterone in order to prevent pregnancy caused by sexual violence, in this sense, this article aims to carry out a survey detailed bibliographic information about the lack of restricted information and the possible consequences that the excessive use of EC can cause to women's health, in order to alert mainly young people and women who purchase and use this medication, so that its rational and can be promoted by preventing or reducing its use. Method: This article was structured based on a descriptive literature review, exploring and conducting data surveys with evidence in books and scientific articles. Searches were performed in the following databases: Scielo (Scientific Electronic Library Online), Ministry of Health, VHL (Virtual Health Library). NIH (National Library of Medicine). Results and discussion: Young people between 15 and 20 years of age are the ones who most consume EC mainly because they have sexual intercourse without a condom, studies show that they are unaware of its pharmacodynamics and maximum efficacy index. Final considerations: The EC has been shown to be effective as an emergency method of choice, provided that it is used within the established timeframe, that is, the sooner its use, the greater its effectiveness. In this sense, it is important to emphasize that the use of this method should only be performed when it is really necessary.